Exploration of T cell immune responses by expression of a dominant-negative SHP1 and SHP2 - Taylor, Julia; Bulek, Anna; Gannon, Isaac; Robson, Mathew; Kokalaki, Evangelia; Grothier, Thomas; McKenzie, Callum; El-Kholy, Mohamed; Stavrou, Maria; Traynor-White, Charlotte; Lim, Wen Chean; Panagiotou, Panagiota; et al. (Frontiers in Immunology, 2023)
SHP1 and SHP2 are SH2 domain-containing proteins which have inhibitory phosphatase activity when recruited to phosphorylated ITIMs and ITSMs on inhibitory immune receptors. Consequently, SHP1 and SHP2 are key proteins in the transmission of inhibitory signals within T cells, constituting an important point of convergence for diverse inhibitory receptors. Therefore, SHP1 and SHP2 inhibition may represent a strategy for preventing immunosuppression of T cells mediated by cancers hence improving immunotherapies directed against these malignancies. Both SHP1 and SHP2 contain dual SH2 domains responsible for localization to the endodomain of inhibitory receptors and a protein tyrosine phosphatase domain which dephosphorylates and thus inhibits key mediators of T cell activation. We explored the interaction of the isolated SH2 domains of SHP1 and SHP2 to inhibitory motifs from PD1 and identified strong binding of both SH2 domains from SHP2 and more moderate binding in the case of SHP1. We next explored whether a truncated form of SHP1/2 comprising only of SH2 domains (dSHP1/2) could act in a dominant negative fashion by preventing docking of the wild type proteins. When co-expressed with CARs we found that dSHP2 but not dSHP1 could alleviate immunosuppression mediated by PD1. We next explored the capacity of dSHP2 to bind with other inhibitory receptors and observed several potential interactions. In vivo we observed that the expression of PDL1 on tumor cells impaired the ability of CAR T cells to mediate tumor rejection and this effect was partially reversed by the co-expression of dSHP2 albeit at the cost of reduced CAR T cell proliferation. Modulation of SHP1 and SHP2 activity in engineered T cells through the expression of these truncated variants may enhance T cell activity and hence efficacy in the context of cancer immunotherapy.